TEACHER'S PEDAGOGICAL COMPETENCE IN THE ERA OF DISRUPTION 4.0 EDUCATION - Purwaningsih, Ega; Madhakomala, R; Rita, Rita (IJBLE Scientific Publications Community Inc., 2022)
Based on the national education system, education is a conscious and deliberate effort to create an atmosphere and learning effort that allows students to actively expand their potential because they play religious and spiritual strengths, self-operation, character, intelligence, noble character, and essential requirements. Technology characterizes self, society and society. countries and states. At this point, teachers are expected to have the personality to manage learning programs appropriately and in harmony with student needs. This article aims to explain the necessity of reviewing the pre-education curriculum in LPTKs, especially those related to educational philosophy issues, and proposes regulatory support that can support the realization of professional pedagogic competencies. The ability of teacher education must be improved not only in terms of the ability of teachers, but also philosophically in education itself. In the future, educators are expected to be able to adapt and even be creative in order to create disruptive innovations in order to improve the quality of education. This article also suggests a more targeted curriculum review and government support as a solution.